1991
DOI: 10.1002/jcp.1041470102
|View full text |Cite
|
Sign up to set email alerts
|

Structural/functional relationships between internal and external MSH receptors: Modulation of expression in Cloudman melanoma cells by UVB radiation

Abstract: Expression of internal receptors for MSH is an important criterion for responsiveness to MSH by Cloudman melanoma cells (Orlow et al: J. Cell. Physiol., 142:129-136, 1990). Here, we show that internal and external receptors for MSH are of identical molecular weights (50-53 kDa) and share common antigenic determinants, indicating a structural relationship between the 2 populations of molecules. The internal receptors co-purified with a sub-cellular fraction highly enriched for small vesicles, many of which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 28 publications
4
58
0
1
Order By: Relevance
“…All three agents, like pTpT, enhanced melanin content per cell 4-10-fold in S91 cells and by up to 70% in human melanocytes. These agents also induced tyrosinase mRNA levels and MSH binding to its cell surface receptor (67), as has been reported for ultraviolet irradiation (68,69). Because Pvu 11, MMS and 4-NQO are known to interact with DNA and to produce DNA lesions that are repaired in a manner similar to those produced by ultraviolet irradiation, these results further strengthen the hypothesis that UV light induces melanogenesis at least in part as a direct consequence of its effects on DNA.…”
Section: The Role Of Dna Damagwrepair In Uv-induced Melanogenesissupporting
confidence: 81%
“…All three agents, like pTpT, enhanced melanin content per cell 4-10-fold in S91 cells and by up to 70% in human melanocytes. These agents also induced tyrosinase mRNA levels and MSH binding to its cell surface receptor (67), as has been reported for ultraviolet irradiation (68,69). Because Pvu 11, MMS and 4-NQO are known to interact with DNA and to produce DNA lesions that are repaired in a manner similar to those produced by ultraviolet irradiation, these results further strengthen the hypothesis that UV light induces melanogenesis at least in part as a direct consequence of its effects on DNA.…”
Section: The Role Of Dna Damagwrepair In Uv-induced Melanogenesissupporting
confidence: 81%
“…Previous work on the upregulation of tyrosinase activities and melanin synthesis in cultured melanocytes by -MSH indicated that this POMC peptide was implicated in the regulation of melanogenesis (McLane & Pawelek 1988, Chakraborty et al 1991, Pawelek et al 1992. However, the mechanism of action remained unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Both -MSH and ACTH are proposed to be the key players in pigmentation via the melanocortin-1-receptor (MC1-R)/ cAMP second messenger system (Tsatmali et al 1999(Tsatmali et al , 2000. Moreover, it was shown that -MSH stimulates changes in melanocyte morphology, growth rates and melanin production (McLane & Pawelek 1988, Chakraborty et al 1991. However, its mode of action is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings that human melanocytes respond directly to subnanomolar concentrations of these two melanotropins, the presence of MSH receptors on human melanocytes (14)(15)(16)(17), and the demonstration that melanotropins are present in the skin (21) suggest a physiologic paracrine role for these hormones in regulating human pigmentation. Irradiation of murine melanoma cells with ultraviolet light activates the melanotropin receptor (35,36), and mutations in the melanotropin receptor lead to pigmentary changes in several mammalian species (37). That melanotropins might be involved in the sun-induced melanogenic effects on human skin and that mutations in the melanotropin receptor might be responsible for pigmentary abnormalities in humans are exciting possibilities that are yet to be explored.…”
Section: Discussionmentioning
confidence: 99%